A Biocompatible Endothelial Cell Delivery System for In Vitro Tissue Engineering - Lee, Eun Jung (2009)
Engineering solid tissues, including cardiac muscle, requires the inclusion of a microvasculature. Prevascularization in vitro will likely be dependent upon coculturing parenchymal cells with vascular cells, on a matrix that is sufficiently porous to allow microvessel formation. In this study, we examined the behavior and function of endothelial cells on a highly porous elastomeric 3D poly(glycerol sebacate) (PGS) scaffold, to provide a flexible and biocompatible endothelial cell delivery system for developing cardiac engineered tissues with neovascularization potential. Both static and perfusion cell seeding methods were used, and the effects of surface treatment of the scaffold with various extracellular matrix components were examined. Endothelial cell adhesion and phenotype on the PGS scaffold under various flow conditions were also determined. Surface coating with laminin markedly improved the endothelial cell adhesion, survival, and proliferation. The anticoagulant phenotype of adhered endothelial cells was further regulated by the application of flow through regulation of nitric oxide expression. By providing a highly porous scaffolding that contains endothelium with anticoagulant properties, the endothelial cell-seeded PGS scaffold could provide a new basis for subsequent coculture studies with various cell types to develop complex engineered tissue constructs with vascularization capacity.